Ethanol sclerotherapy for endometriomas: a fertility-preserving alternative - Younis, Johnny S. (Frontiers in Reproductive Health, 2025)
Endometriomas are a common manifestation of endometriosis in women of reproductive age and pose a clinical challenge due to their association with pain, infertility, and compromised ovarian reserve. Surgical removal through cystectomy remains the standard intervention, but compelling evidence demonstrates its deleterious impact on ovarian reserve and potential acceleration of ovarian aging. These concerns have prompted an investigation of less invasive alternatives. Among these, ethanol sclerotherapy has emerged as a promising, minimally invasive, often ultrasound-guided procedure offering cyst resolution with minimal trauma to ovarian tissue. This mini-review synthesizes current evidence on ethanol sclerotherapy for the management of endometriomas, with an emphasis on clinical outcomes and implications for fertility preservation. Evidence indicates that ethanol sclerotherapy is highly effective technically, with low rates of major complications. Pain relief is achievable, recurrence rates can be reduced with longer ethanol exposure, and ovarian reserve is preserved compared with cystectomy. Assisted reproduction outcomes suggest comparable pregnancy rates, with some data supporting a higher oocyte yield following sclerotherapy. Nevertheless, the quality of evidence is limited, predominantly derived from observational studies, and results vary regarding long-term efficacy and reproductive outcomes. Ethanol sclerotherapy is best considered a minimally invasive, fertility-sparing option for women seeking to avoid surgery or preserve reproductive potential. Future randomized controlled trials should clarify its role relative to cystectomy and expectant management, establish optimal procedural parameters, and assess long-term outcomes, including ovarian reserve, live birth rates, and cost-effectiveness.